Efficacy of physical therapy associated with botulinum toxin type A on functional performance in post-stroke spasticity: A randomized, double-blinded, placebo-controlled trial - Antonio Prazeres; Marília Lira; Paula Aguiar; Larissa Monteiro; Ítalo Vilasbôas; Ailton Melo (MDPI AG, 2018)
The aim was to investigate if botulinum toxin type A (BTx-A) associated with physical therapy is superior to physical therapy alone in post stroke spasticity. A randomized, double-blinded controlled trial was performed in a rehabilitation unit on Northeastern, Brazil. Patients with post stroke spasticity were enrolled either to BTx-A injections and a pre-defined program of physical therapy or saline injections plus physical therapy. Primary endpoint was functional performance evaluated through time up and go test, six minutes walking test and Fugl-Meyer scale for upper limb. Secondary endpoint was spasticity improvement. Confidence interval was considered at 95%. Although there was a significant decrease in upper limbs flexor tonus (P<0.05) in the BTx-A group, there was no difference regarding functional performance after 9 months of treatment. When analyzing gait speed and performance, both groups showed a significant improvement in the third month of treatment, however it was not sustained over time. Although BTx-A shows superiority to improve muscle tone, physical therapy is the cornerstone to improve function in the upper limbs of post stroke patients.